Noctilucent cloud variability and mean parameters from 15 years of lidar observations at a mid‐latitude site (54°N, 12°E). Issue 2 (17th January 2013) - Gerding, M.; Höffner, J.; Hoffmann, P.; Kopp, M.; Lübken, F.‐J.
Abstract : [1] Noctilucent clouds (NLC) are an important tracer of temperature and dynamics of the summer mesopause region. Our site at Kühlungsborn (Germany, 54°N) is at the equatorward edge of the NLC region and therefore of special interest for the understanding of these clouds. 41 nights (63 h) of NLC are observed since 1997. They form the largest lidar data set from mid‐latitudes. NLC are typically weak, with nearly 70% having a backscatter coefficient β max, 532nm  < 2 ⋅ 10 −10 m −1 sr −1 . The seasonal variation of NLC shows maximum occurrence around the temperature minimum (saturation maximum) but lower temperatures (higher saturation) at the beginning compared to the end of the season. Mean centroid altitude is 82.7 ± 0.03 km, with strong NLC being typically lower and vertically thinner compared to weak clouds. NLC occurrence was lowest in the years 2000–2002 and reached a maximum in 2009 with a rate of 19%. Overall, NLC are less frequent and dimmer compared to higher latitudes. The occurrence is highly anti‐correlated with solar activity. Beside NLC, we are measuring mesospheric temperatures since 2002 by lidars, complemented by microwave observations of water vapor (since October 2009) and radar observations of mesospheric winds. NLC occurrence is found anti‐correlated with ambient temperatures ( r  = −0.85 at 84 km), while low temperatures are necessary but not sufficient for individual events. Meridional winds at 84 km are weakly anti‐correlated with NLC occurrence ( r  = −0.58 at 84 km). Furthermore, we find some biennial variation of NLC occurrence in part of the time series. Any additional trend has not yet been detected. Key Points: 15 years of mid‐latitude NLC data: less and weaker NLC than at polar latitudes Temperatures influence mean NLC occurrence while not sufficient for individual Mean NLC height only 700 m below polar NLC despite strong temperature difference